Efficient, stable, and reusable silicoaluminophosphate for the one-pot production of furfural from hemicellulose - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (ACS Catalysis, 2013)
Development of stable, reusable, and water tolerant solid acid catalysts in the conversion of polysaccharides to give value-added chemicals is vital because catalysts are prone to undergo morphological changes during the reactions With the anticipation that silicoaluminophosphate (SAPO) catalysts will have higher hydrothermal stability, those were synthesized, characterized, and employed in a one-pot conversion of hemicellulose. SAPO-44 catalyst at 170 degrees C within 8 h could give 63% furfural yield with 88% mass balance and showed similar activity up to at least 8 catalytic cycles. The morphological studies revealed that SAPO catalysts having hydrophilic characteristics are stable under reaction conditions.
Keywords: furfural; Hemicellulose; hydrophilicity; SAPO; water-tolerant catalyst; zeolite